Enhancing Students' Engagement in Learning English Through Non-Digital Gamification - Mardiah, Radiatan; Desi, Desi (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Abstract The study investigates the use of non-digital gamification in junior high school English learning, involving seven graders in Jambi Province. The research used Classroom Action Research and two cycles of gamification. Results showed that students found the learning process more interesting and stimulating, with engagement levels significantly increasing. The implementation of each cycle resulted in a 22.5% overall increase in engagement.